Study Participant Flow Diagram. - Fred C. Semitala (4386067) (2025)
Access to antiretroviral therapy has led to better treatment outcomes for aging people living with HIV worldwide. However, in Uganda and other parts of sub-Saharan Africa, PLHIV with comorbidities like hypertension experience fragmented healthcare access, despite existing guidelines for the integration of non-communicable diseases into HIV care. We assessed knowledge, attitudes, and practices of PLHIV regarding hypertension care, and their perceptions of integrated hypertension-HIV care. We used a parallel convergent-mixed methods approach to collect quantitative and qualitative data from HIV clinics in urban and peri-urban Uganda. We surveyed PLHIV with hypertension to explore their knowledge, attitudes, and practices related to HTN. We selected a sub-sample from survey participants for qualitative interviews, to explore their perceptions of hypertension care and integrated HTN and HIV services. We analyzed quantitative data using STATA 14.1 and analyzed qualitative data deductively mapping it onto the Consolidated Framework for Implementation Research. A total of 394 PLHIV (325 in Kampala and 69 in neighboring Wakiso district) were enrolled in the study. Their median age was 52 years (IQR 44–59), and 300 (76%) were female. Only 32% of the participants correctly identified the normal range for systolic blood pressure (BP) (80–140 mmHg) and 24% diastolic BP (60–90 mmHg). Although 87% of the participants recognized that hypertension was treatable, only 62% knew that the treatment was lifelong. Barriers identified through interviews included fragmented care delivery, frequent hypertension medication shortages, interruptions due to side effects, high out of pocket costs of hypertension drugs, use of herbal remedies, and PLHIV discontinuing medication upon feeling better. Integrating chronic care for co-morbidities like hypertension in HIV clinics in Uganda offers an opportunity to address key barriers, including knowledge gaps, inconsistent medication access, and fragmented care delivery. The findings of this formative assessment informed the development of strategies to integrate hypertension-HIV care in Uganda.